Environmental Impact 2012
DOI: 10.2495/eid120201
|View full text |Cite
|
Sign up to set email alerts
|

Organic and conventional date farm efficiency estimation, and its determents at Riyadh province, Kingdom of Saudi Arabia

Abstract: This paper aims to estimate efficiencies of input use and its determinants using a two step methodology. First, to estimate the efficiency of conventional and organic date farms in Saudi Arabia, with special reference to the Riyadh province. Second, to show the impacts of relative input use, as an indicator of technology level and specialization degree, as efficiency determinants. Riyadh Province has the main date production and date area, it reaches 23% and 25% of total production and area of dates respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Tzouvelakas et al [37], analysing the olive sector in Greece applying a Stochastic Frontier Analysis (SFA), found that organic crop is more efficient than conventional farming. On the other hand, the Data Envelopment Analysis (DEA) technique applied on the studies of Damara et al [38], Alkahtani and Elhendy [39], Beltrán-Esteve and Reig-Martínez [40], confirms the greater efficiency of conventional farms respectively as production, total revenue and sales are concerned. In the same vein, Madau [34] and Serra and Goodwin [41], using the SFA to analyse the cereal sector in Italy and Spain, respectively, concluded that conventional farms are more efficient in terms of income and production terms.…”
Section: Introductionmentioning
confidence: 98%
“…Tzouvelakas et al [37], analysing the olive sector in Greece applying a Stochastic Frontier Analysis (SFA), found that organic crop is more efficient than conventional farming. On the other hand, the Data Envelopment Analysis (DEA) technique applied on the studies of Damara et al [38], Alkahtani and Elhendy [39], Beltrán-Esteve and Reig-Martínez [40], confirms the greater efficiency of conventional farms respectively as production, total revenue and sales are concerned. In the same vein, Madau [34] and Serra and Goodwin [41], using the SFA to analyse the cereal sector in Italy and Spain, respectively, concluded that conventional farms are more efficient in terms of income and production terms.…”
Section: Introductionmentioning
confidence: 98%